THE COMPARETIVE ANALYSIS OF ADJECTIVES IN ENGLISH AND UZBEK LANGUAGES - Muhammedov Aziz Shavkatovich, Qiyomova Sevara Erkinjon qizi, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article is devoted to the usage and draws an analogy to adjectives by the levels of morphology in two different languages. Adjectives are seen in particularly different ways by Eastern and Western linguists, and even within setting to set side by sidein order to show differences and likenesses. The past is over, but present you can seize, and make it for you in the immediate future. So, there are some similar and different features of adjectives which we have tried to demonstrate in English and Uzbek languages.